2005
DOI: 10.1007/s00122-005-2014-8
|View full text |Cite
|
Sign up to set email alerts
|

SSR allelic diversity changes in 480 European bread wheat varieties released from 1840 to 2000

Abstract: A sample of 480 bread wheat varieties originating from 15 European geographical areas and released from 1840 to 2000 were analysed with a set of 39 microsatellite markers. The total number of alleles ranged from 4 to 40, with an average of 16.4 alleles per locus. When seven successive periods of release were considered, the total number of alleles was quite stable until the 1960s, from which time it regularly decreased. Clustering analysis on Nei's distance matrix between these seven temporal groups showed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
109
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 15 publications
14
109
1
Order By: Relevance
“…In oat, DI ranged from 0.01 to 0.17 with the average of 0.09. In comparison with DI of 0.65 found in wheat analysed with 42 microsatellite loci (Roussel et al 2005), the collections of oat and barley showed a lower level of variability. Diversity index calculated per microsatellite loci (H) ranged from 0.155 to 0.921 with an average of 0.719 in barley and from 0.018 to 0.996 with an average of 0.545 in oat (Table 2).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…In oat, DI ranged from 0.01 to 0.17 with the average of 0.09. In comparison with DI of 0.65 found in wheat analysed with 42 microsatellite loci (Roussel et al 2005), the collections of oat and barley showed a lower level of variability. Diversity index calculated per microsatellite loci (H) ranged from 0.155 to 0.921 with an average of 0.719 in barley and from 0.018 to 0.996 with an average of 0.545 in oat (Table 2).…”
Section: Resultscontrasting
confidence: 54%
“…In addition, microsatellites exhibit a codominant inheritance (Hernández et al 2002), which is essential for effective discrimination between closely related lines (Akkaya et al 1992). Microsatellite markers are currently used to identify genotypes, quantitative trait loci (QTLs) and genetic diversity (Leišová & Ovesná 2001;Medini et al 2005;Roussel et al 2005).…”
mentioning
confidence: 99%
“…The higher proportion of genetic variation explained by the cultivars within the clusters indicated a large variation among the cultivars within a cluster as a result of intensive breeding activities within each breeding program, which made use of diverse genetic materials while selecting for local adaptation. Roussel et al (2005) also reported similar trends of larger withingroup genetic variation in wheat cultivars from different regions of Europe. Our results suggest that a significant amount of genetic diversity was incorporated into the HRWW cultivars in this study.…”
Section: Genetic Diversity In the Hrww Cultivarssupporting
confidence: 58%
“…Landraces are the only primary gene pool for bread wheat. To broaden the available genetic resources and to interpret the process of wheat spreading, the genetic diversity of wheat landraces has been investigated by a number of studies (Tsujimoto et al 1998, Bhattacharya et al 1999, Iwaki et al 2001, Ghimire et al 2005, Roussel et al 2005, Tanaka et al 2005, Balfourier et al 2007. Several studies using wheat landraces have achieved success in introducing useful agronomic traits such as semi-dwarfness (Borlaug 1968), disease resistance (Rudd et al 2001), and preferable flour quality (Nakamura et alprotein is encoded by three homoeologous loci located on group 1 chromosomes (Payne et al 1980, Lawrence andShepherd 1981).…”
Section: Introductionmentioning
confidence: 99%